(untitled) (Raparin Journal of Humanities (RJH), 2026)
This study aims to find the merits and shortcomings of Native English-Speaking Teachers and Non-Native English-Speaking Teachers in teaching listening and speaking courses through gender and group analysis across five dimensions: teacher’s personality traits, professionalism, pedagogical approach, cultural competence, and linguistic competence. To achieve this aim, a descriptive survey design was employed using a mixed-methods approach. Quantitative data were collected through a structured questionnaire administered to 100 students, whereas qualitative insights were obtained from semi-structured interview with 10 students. All participants enrolled were third-year students in the Department of English Language, College of Basic Education, University of Duhok. The research collected both quantitative and qualitative data from participants of both genders who belonged to three different Groups. The quantitative data were analyzed using SPSS 24 to calculate percentage, Chi-square tests, and significance values (p), while thematic analysis was used for qualitative data. The findings show that both types of teachers have their own strengths; Native English-Speaking Teachers are more effective in pronunciation and natural fluency, while Non-Native English-Speaking Teachers are more effective in grammar and structural clarity. However, the contradiction between questionnaire results and interview insights reveal that students have different attitudes towards the two types of teachers, which are influenced by the clarity of instruction and the accessibility of communication. Implications for teacher training and curriculum development are discussed.